The son [videorecording (DVD)] - Zeller, Florian; Hampton, Christopher, 1946-; Jackman, Hugh; Dern, Laura; Kirby, Vanessa; McGrath, Zen; Quarshie, Hugh; Hopkins, Anthony, 1937-; Zeller, Florian (Sony Pictures Home Entertainment, 2023)
A cautionary tale that follows a family as it struggles to reunite after falling apart. Centers on Peter, whose hectic life with his infant and new partner Beth is upended when his ex-wife Kate appears at his door to discuss their son Nicholas, who is now a teenager. The young man has been missing school for months and is deeply troubled. Peter strives to take care of Nicholas as he would have wanted his father to have taken care of him while juggling his and Beth's new son, and at work an offer of a dream position in Washington. However, by reaching for the past to correct its mistakes, he loses sight of how to hold onto Nicholas in the present.